2018
DOI: 10.4103/0366-6999.243934
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP3A4*1G Polymorphism on Fentanyl Analgesia Assessed by Analgesia Nociception Index in Chinese Patients Undergoing Hysteroscopy

Abstract: Background:The clinical efficacy of fentanyl for pain control differs greatly across individuals. The purpose of this study was to investigate the impact of CYP3A4*1G polymorphism including wild-type homozygote (CYP3A4*1/*1, GG), mutant heterozygote (CYP3A4*1/*1G, GA), and mutant homozygote (CYP3A4*1G/*1G, AA) on fentanyl analgesia in Chinese patients undergoing hysteroscopy by the assessment of analgesia nociception index (ANI).Methods:A total of 200 gynecologic patients scheduled for elective hysteroscopy un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In clinical practice, in order to relieve postoperative pain and inflammation, analgesic measures are usually taken before the injury acts on the body. is treatment is clinically called preemptive analgesia [15]. Oxycodone, as an opioid μ and κ double receptor agonist, took effect 2 min after intravenous injection and peaked at 5 min, lasting for about 3.5 h, without causing histamine release and bradycardia, or inhibiting the parasympathetic nerve, thus exerting a better inhibitory effect on visceral pain [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, in order to relieve postoperative pain and inflammation, analgesic measures are usually taken before the injury acts on the body. is treatment is clinically called preemptive analgesia [15]. Oxycodone, as an opioid μ and κ double receptor agonist, took effect 2 min after intravenous injection and peaked at 5 min, lasting for about 3.5 h, without causing histamine release and bradycardia, or inhibiting the parasympathetic nerve, thus exerting a better inhibitory effect on visceral pain [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Fentanyl is known to be metabolized by Cytochrome P450 (CYP) enzymes, CYP3A4 and CYP3A5. Specifically CYP3A4*1G, CYP3A5*3, and CYP3A5*6 alleles have been shown to affect fentanyl PKs in adults, [9][10][11][12][13][14] although not all studies have reported significant effects. 15 Fentanyl clearance is reduced in neonates and rapidly matures in the first month of life, 16 likely due in part to the maturation of CYP3A encoded enzymes.…”
Section: Articlementioning
confidence: 99%
“… 1 Propofol alone or combined with opioid μ receptor agonists, such as fentanyl and sufentanil, are current the anesthetic methods used for painless hysteroscopy. 6 , 7 However, propofol has a weak analgesic effect and injection pain, 8 while opioid μ receptor agonists are associated with an increased risk of respiratory depression, nausea and vomiting, 9 which are unexpected for both patients and anesthesiologists. Therefore, the anesthetic strategies still need to be improved.…”
Section: Discussionmentioning
confidence: 99%